NILAI NILAI PENDIDIKAN AGAMA ISLAM DALAM TRADISI HAROA MASYARAKAT BUTON KELURAHAN LAMANGGA KOTA BAUBAU - Fawal Fatwa Muslimin; Abdul Rahim; Laode Sahrin Djalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the values of Islamic religious education contained in the Haroa tradition of the Buton community in Lamangga Village, Baubau City, and its relevance in socio-religious life. The Haroa tradition is a collective prayer and thanksgiving practice carried out on various important occasions as a form of gratitude to Allah SWT. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the Haroa tradition contains Islamic educational values, including aqidah (faith), worship, morality, and social values. The value of aqidah is reflected in the belief in Allah through collective prayers, worship values are seen in the practice of dhikr and recitation of the Qur'an, moral values are reflected in mutual respect and togetherness, while social values are manifested in cooperation and community solidarity. Furthermore, the Haroa tradition is highly relevant as a medium for Islamic education based on local culture through non-formal value internalization processes. However, this tradition faces challenges in the era of modernization, particularly in the shifting understanding of its religious meaning among younger generations. Therefore, efforts are needed to preserve and strengthen Islamic educational values within the Haroa tradition to maintain its relevance in contemporary society.